ANALISIS EFISIENSI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI USAHATANI CABAI RAWIT DI DESA GIRIKULON KECAMATAN SECANG KABUPATEN MAGELANG - Nila Maemunah; Bambang Mulyatno S; Agus Setiadi (Universitas Tadulako, 2019)
The research aimed to analyze the effect of the use of production factors such as land, seed, manure, ZA fertilizer, TSP fertilizer, KCL fertilizer and pesticide and to analyze the economic and technical efficiency of factors affecting chili farming in Girikulon village, Secang district, Magelang regency. The method used in this research was survey. The research was conducted in January-February 2019 in Girikulon Village, Secang District, Magelang regency. The location of the research was selected purposively. Samples were taken using a probability sampling technique on 33 farmers who exclusively practiced monoculture chili cultivation. Data was analyzed using multiple linear regression analysis method transformed into the Cobb-Douglas model production function and analysis of technical efficiency and economic. The economic efficiency tested employed a different sample analysis (one sample T test). The results showed that the use of production factors i.e. land, seed, labor, manure, ZA fertilizer and pesticide simultaneously had significant effect on the yields while the other factors such as TSP and KCL fertilizer had no significant effect on the yield. The use of land, KCL fertilizer and pesticide was technically and economically not efficient. Keywords: Chili, Efficiency and Factors Of Production.